The impact of human-computer interaction on electronic service quality satisfaction towards Taobao online platform: mediated by task technology fit - Ruan, Qijie; Li, Mengyu; Wan Abas, Wan Anita; Hassan, Abd Rauf; Liu, Huinan (Informa UK Limited, 2023)
How human-computer interaction affects customer electronic service quality satisfaction is an important issue that electronic service-based companies need to consider. This paper constructs a conceptual model based on service dominant logic theory and task technology fit theory. It conducts a questionnaire survey of 559 Taobao platform users to verify the proposed hypothesis. The results show that human-computer interaction comprises three basic factors (technology functionality, task routineness, and technology readiness) and two core factors (interaction between task routineness and technology functionality, and interaction between technology readiness and technology functionality). This research enriches the theoretical basis of electronic service quality. It promotes the development of task technology fit theory in service science, providing guidance for electronic service-based companies to improve service interfaces and enhance electronic service quality.